German Heart Surgery Report 2016: The Annual Updated Registry of the German Society for Thoracic and Cardiovascular Surgery - Beckmann, Andreas; Funkat, Anne-Katrin; Lewandowski, Jana; Frie, Michael; Ernst, Markus; Hekmat, Khosro; Schiller, Wolfgang; Gummert, Jan F.; Harringer, Wolfgang (The Thoracic and Cardiovascular Surgeon, 2017)
Based on a long-standing voluntary registry founded by the German Society for Thoracic and Cardiovascular Surgery (GSTCVS), well-defined data of all cardiac, thoracic, and vascular surgery procedures performed in 78 German heart surgery departments during the year 2016 are analyzed. In 2016, a total of 103,128 heart surgery procedures (implantable defibrillator, pacemaker, and extracardiac procedures excluded) were submitted to the registry. Approximately 15.7% of the patients were at least 80 years of age, resulting in an increase of 0.9% compared with the data of 2015. For 37,614 isolated coronary artery bypass grafting procedures (relationship on-/off-pump 4.4:1), an unadjusted in-hospital mortality of 2.9% was observed. Concerning the 33,451 isolated heart valve procedures (including 11,701 catheter-based procedures), the unadjusted in-hospital mortality was 4.3%.This annual updated registry of the GSTCVS represents voluntary public reporting by accumulating actual information for nearly all heart surgical procedures in Germany, describes advancements in heart medicine, and is a basis for internal and external quality assurances for all participants. In addition, the registry demonstrates that the provision of cardiac surgery in Germany is appropriate and patients are treated nationwide at all times.
Keywords: heart surgery; outcomes; registry; quality assurance; congenital heart disease; aortic surgery